Measuring Perseverance and Passion in Distance Education Students: Psychometric Properties of the Grit Questionnaire and Associations With Academic Performance - Xu, Kate M.; Meijs, Celeste; Gijselaers, Hieronymus J. M.; Neroni, Joyce; de Groot, Renate H. M. (Frontiers in Psychology, 2020)
With modern technological advances, distance education has become an increasingly important education delivery medium for, for example, the higher education provided by open universities. Among predictive factors of successful learning in distance education, the effects of non-cognitive skills are less explored. Grit, the dispositional tendency to sustain trait-level passion and long-term goals, has raised much research interest and gained importance for predicting academic achievement. The Grit Questionnaire, measuring Perseverance of Effort and Consistency of Interests, has been shown to be a reliable instrument in traditional university student populations. However, the measurement and predictive validity of this questionnaire is still unknown for adult distance education university students who differ from traditional students in various ways (e.g., having a wider range of student ages). Based on a sample of 2,027 students from a distance education university, this study assessed the psychometric properties of the two-factor structure grit measured by the Grit Questionnaire. The findings suggest that the short form of the Grit Questionnaire is a potentially useful assessment tool for measuring the grit construct for distance learning higher education and that the Consistency of Interests factor is especially relevant to consider the improvement of learning performance for distance education in terms of courses credit and exam attempts. The measurement precision of the Perseverance of Effort factor, however, should be improved in future research to provide higher measurement accuracy and broader item coverage.